2012
DOI: 10.1097/yic.0b013e32834d0e50
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of naltrexone for dissociative symptoms in borderline personality disorder

Abstract: Data from a pilot study suggest that naltrexone might reduce dissociative symptoms in patients with borderline personality disorder. However, the interpretation of these data is limited by the lack of a control group and by the nonblind nature of this study. Hence, we examined the effects of naltrexone using a more rigorous design that controlled for major confounders such as spontaneous reduction of dissociation over time and placebo effects. Unmedicated patients with BPD [according to Diagnostic and Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 0 publications
0
14
0
10
Order By: Relevance
“…Furthermore, an open label study showed reduction of dissociative symptoms in BPD females [41]. This finding could not be confirmed by a small cross-over placebo controlled study, perhaps due to the low power of the study [42]. Additionally, another RCT evaluating nalmefene in patients with BPD with comorbid alcohol abuse showed a significant reduction in heavy drinking days and a reduction in a BPD symptom list and CGI-BPD [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an open label study showed reduction of dissociative symptoms in BPD females [41]. This finding could not be confirmed by a small cross-over placebo controlled study, perhaps due to the low power of the study [42]. Additionally, another RCT evaluating nalmefene in patients with BPD with comorbid alcohol abuse showed a significant reduction in heavy drinking days and a reduction in a BPD symptom list and CGI-BPD [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although this is largely correct, there are some limited data on pharmacotherapy for dissociative symptoms. Several open trials 78 and one RCT 79 have suggested that naltrexone may help to reduce dissociative symptoms and posttraumatic flashbacks in borderline patients. Others have described its effectiveness in reducing self-injurious behavior in dissociative identity disorder.…”
Section: Pharmacotherapy Of Dissociationmentioning
confidence: 98%
“…A recent review supported the efficacy of SSRIs, in particular fluoxetine for impulsivity and affective symptoms; mood stabilizers among which valproate, topiramate, and lamotrigine demonstrated efficacy for affective symptoms related to anger and impulsive aggression; olanzapine was the most efficacious among second generation antipsychotics in targeting aggressiveness, affective and cognitive-perceptual symptoms [63]. Furthermore, recent efficacy studies point to novel drugs, such as opioid antagonist [64,65], clonidine [66,67], omega-3 fatty acids [68][69][70], and oxytocin [71][72][73] in reducing affective instability, impulsivity, self -injuries, and dissociative symptoms. Fundamentally, the abundance of options with poorly specified benefits have encouraged polypharmacy, which sometimes leads to undesirable side effects [74].…”
Section: 2) Pharmacotherapy For Bpdmentioning
confidence: 97%